The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1159/000368995
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing RBC Alloimmunization: Lessons Learned from Murine Models

Abstract: Red blood cell (RBC) alloimmunization may occur following transfusion or pregnancy/delivery. Although observational human studies have described the immunogenicity of RBC antigens and the clinical significance of RBC alloantibodies, studies of factors influencing RBC alloimmunization in humans are inherently limited by the large number of independent variables involved. This manuscript reviews data generated in murine models that utilize transgenic donor mice, which express RBC-specific model or authentic huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 104 publications
(146 reference statements)
1
74
0
1
Order By: Relevance
“…It has been suggested that the characteristics of EVs can vary among the blood products due to the variation in the blood processing methods [51,52]. An article by Bakkour et al [19] highlighted some feasible reasons to explain the variation in EV characteristics between RCF and WBF RCCs, including variability in the temperature and the lengths of pre-processing storage time as well as leukoreduction technique.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the characteristics of EVs can vary among the blood products due to the variation in the blood processing methods [51,52]. An article by Bakkour et al [19] highlighted some feasible reasons to explain the variation in EV characteristics between RCF and WBF RCCs, including variability in the temperature and the lengths of pre-processing storage time as well as leukoreduction technique.…”
Section: Discussionmentioning
confidence: 99%
“…10 Once exposed, the maternal immune system may or may not respond to foreign red cell antigens. 11 The immune response to red cell antigens is complex and not fully understood. It is clear that the RhD antigen is the most potent immunogen of all of the red cell antigens; 85% of RhD-negative individuals will sensitize (form anti-D) after challenge with a 200 mL transfusion of red cells, although more recent data suggests this is far lower.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…In transfusion medicine, immune responses to allogeneic RBCs represent a significant obstacle to multiple transfusions in clinical practice. Despite decades of experience in the transfusion of RBCs and the observation of a multitude of allo-antibodies thereafter, the precise mechanisms by which transfused RBCs induce alloantibody formation in certain individuals and in certain clinical scenarios remain to be fully understood and they are the subject of extensive investigation and are reviewed elsewhere [34,35]. …”
Section: Rbc As Carriers In Drug Delivery: Brief Overviewmentioning
confidence: 99%